A novel approach for preparing in-situ nitrogen doped carbon via pyrolysis of bean pulp for supercapacitors. (1st February 2021) - Ding, Yan; Li, Yunchao; Dai, Yujie; Han, Xinhong; Xing, Bo; Zhu, Lingjun; Qiu, Kunzan; Wang, Shurong
Abstract: The preparation of activated carbon by complex and expensive nitrogen doping and activation process has been studied extensively. N-doped activated biochar or carbon material prepared from renewable and low-cost biomass has arisen more and more attention due to the hierarchical porous structure and abundant nitrogenous functional groups in the application of supercapacitors. Herein, a method for preparation of in-situ nitrogen doped activated carbon derived from bean pulp (BPC) by one-step carbonization and CO2 activation at 1073 K was proposed. The morphological structure, specific surface area (SSA), pore size and nitrogen-containing functional group compounds could be controlled by the adjustment of CO2 concentration. The maximum SSA could be up to 558.2 m 2 g −1 for BPC. The N content increased from 5.0% to 10.0% with the increase of CO2 concentration from 0 to 50 vol%. In addition, pyridine, pyrrole, graphite, and nitrous oxide were detected and analyzed, in which pyridine and pyrrole nitrogen enhance the pseudocapacitance. A maximum specific capacitance of BPC-50 reached 106 F g −1 at 0.25 A g −1 . The capacitance retention maintained 93% at 10 A g −1 after 20, 000 cycles in the symmetrical supercapacitor with a 6 M KOH electrolyte. Graphical abstract: Schematic diagram representing synthesis of BPCs. Image 1 Highlights: In-situ N doped porous activated carbon was prepared from bean pulp. Morphology structure and chemical composition were controlled by CO2 concentration. Maximum specific surface area of 558.2 m 2 g −1 for BPC-100. The capacitance of BPC-50 reached 106 F g −1 and maintained 93% after 20, 000 cycles.